Equal and Inclusive Study Experiences for International Students with Disabilities (Comparative & International Education Series, 2021)
in the proposed chapter I will document and critically discuss disabled international students’ participation in specifically English university context. A range of barriers that disabled international students face while studying abroad will be highlighted and insights shared in order to work towards equalising international study experience for all students regardless of their impairments or any other characteristics. The recommendations discussed can then be deployed by a range of international educational organisations to assist in adopting an inclusive culture. The effects of focussing on disabled international students’ experiences have direct ramifications, not only for those that are the central concern of the chapter, but also a diverse array of students with a range of minority backgrounds that would benefit from inclusive practices in education.